Characterizing the effects of morphological microstructures and hydropeaks on fish stranding in rivers - Insulaire, Flora; Lamouroux, Nicolas; Barillier, Agnès; Paillex, Amael; Capra, Hervé; Cattaneo, Franck; Gouraud, Véronique (River research and applications, 2024)
Fish stranding in rivers, due to rapid shoreline dewatering, often occurs during the down‐ramping phase of hydropeaks, which enables peak energy production. Multiple hydropeaking characteristics and river morphology influence stranding, but little is known about the effects of riverbed microstructures. Our goal was to identify how the combination of hydropeaking characteristics and the occurrence of morphological microstructures (e.g., puddles and scour pools) influences fish stranding. For this purpose, we used an extensive dataset of fish stranding observations collected over 3 years in spring at 48 sites along a 50 km‐long reach of the Ain River, France. We aimed (1) to characterize stranding events and their associated fish assemblages and (2) to identify the spatial and temporal determinants of stranding. The occurrence of morphological microstructures was the main factor explaining fish stranding. Scour pools had a strong impact, followed by scour puddles, humid zones, and alluvial puddles. Then, hydropeaking characteristics interacted with morphology and modulated the intensity of stranding. Low flow ranges (low peak flow and low base flow) occurring after periods without hydropeaks induced ‘salmonid fry’ stranding events and ‘super‐stranding’ events (massive stranding of many taxa). Other flow ranges induced ‘regular cyprinid fry’ stranding events. Salmonids were particularly subject to stranding at the beginning of the sampling period. Recommendations are (1) to act in priority on sites where stranding is most likely, by morphological operations or by installing attractive structures in the perennial area and (2) to maintain attractive, perennial habitats in the low flow range of hydropeaks, for example, by increasing base flow.